Colorectal Surgery in Critically Unwell Patients: A Multidisciplinary Approach - Subramaniam, Ashwin; Wengritzky, Robert; Skinner, Stewart; Shekar, Kiran (Clinics in Colon and Rectal Surgery, 2022)
A proportion of patients require critical care support following elective or urgent colorectal procedures. Similarly, critically ill patients in intensive care units may also need colorectal surgery on occasions. This patient population is increasing in some jurisdictions given an aging population and increasing societal expectations. As such, this population often includes elderly, frail patients or patients with significant comorbidities. Careful stratification of operative risks including the need for prolonged intensive care support should be part of the consenting process. In high-risk patients, especially in setting of unplanned surgery, treatment goals should be clearly defined, and appropriate ceiling of care should be established to minimize care that is not in the best interest of the patient. In this article we describe approaches to critically unwell patients requiring colorectal surgery and how a multidisciplinary approach with proactive intensive care involvement can help achieve the best outcomes for these patients.
Keywords: colorectal surgery; emergency surgery; intensive care; anesthetic management; mechanical ventilation